2023
DOI: 10.1111/apha.13924
|View full text |Cite
|
Sign up to set email alerts
|

15N‐labeled dietary nitrate supplementation increases human skeletal muscle nitrate concentration and improves muscle torque production

Abstract: Aim Dietary nitrate (NO3−) supplementation increases nitric oxide bioavailability and can enhance exercise performance. We investigated the distribution and metabolic fate of ingested NO3− at rest and during exercise with a focus on skeletal muscle. Methods In a randomized, crossover study, 10 healthy volunteers consumed 12.8 mmol 15N‐labeled potassium nitrate (K15NO3; NIT) or potassium chloride placebo (PLA). Muscle biopsies were taken at baseline, at 1‐ and 3‐h post‐supplement ingestion, and immediately foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 55 publications
(207 reference statements)
1
26
1
Order By: Relevance
“…In contrast, Kadach et al [2023] recently found that NO3supplementation increased muscle torque throughout the first 90 s of a 300 s bout of repeated maximal isometric knee extensions (3 s contraction, 2 s rest). Notably, however, numerous other investigations have failed to demonstrate any effect of dietary NO3on maximal isometric torque [Esen et al 2022], making the study by Kadach et al [2023] an exception. Regardless, based on the present as well as our previous results, it seems clear that although acute ingestion of NO3enhances maximal muscle speed and hence power in older individuals [Coggan et al 2020a;Gallardo et al 2021], it does not alter fatigability during intense contractile activity in older persons.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…In contrast, Kadach et al [2023] recently found that NO3supplementation increased muscle torque throughout the first 90 s of a 300 s bout of repeated maximal isometric knee extensions (3 s contraction, 2 s rest). Notably, however, numerous other investigations have failed to demonstrate any effect of dietary NO3on maximal isometric torque [Esen et al 2022], making the study by Kadach et al [2023] an exception. Regardless, based on the present as well as our previous results, it seems clear that although acute ingestion of NO3enhances maximal muscle speed and hence power in older individuals [Coggan et al 2020a;Gallardo et al 2021], it does not alter fatigability during intense contractile activity in older persons.…”
Section: Discussionmentioning
confidence: 86%
“…In contrast, Kadach et al [2023] recently found that NO3supplementation increased muscle torque throughout the first 90 s of a 300 s bout of repeated maximal isometric knee extensions (3 s contraction, 2 s rest). Notably, however, numerous other investigations have failed to demonstrate any effect of dietary NO3on maximal isometric torque [Esen et al 2022], making the study by Kadach et al [2023] an exception.…”
Section: Discussionmentioning
confidence: 86%
“…The most consistent effects found in the studies performed are enhancements of skeletal muscle contractile function with increased muscle power and capacity for sprint performance and an increase in muscular energetic efficiency as mentioned above 2,3 . These studies constitute the background of the paper by Kadach et al 4 in this issue of Acta Physiologica, where the authors present the use of isotope labeled nitrate to track the fate of dietary nitrate and its utilization by contracting muscles. In a randomized, crossover study, 10 healthy volunteers consumed 12.8 mmol 15 N‐labeled potassium nitrate (K 15 NO 3 ) or potassium chloride placebo.…”
mentioning
confidence: 68%
“…While for many commercially available supplements meaningful data are, at best, incomplete, examples of promising preventive approaches by nutrient supplementation may potentially be assumed for antioxidants, 17,18 bioactive collagen peptides, 19 and nitrates. 20 In summary, the intricate interplay between nutrition and physiology underscores the critical importance of dietary choices in maintaining optimal health. By understanding the biochemical mechanisms through which nutrients interact with our bodies, we gain insight into the foundation of physiological wellbeing.…”
Section: Nutritional Healthmentioning
confidence: 99%
“…The global dietary supplement markets are growing at almost obscene rates with an increased consumer demand for preventive healthcare and aging populations in developed countries able to afford these products. While for many commercially available supplements meaningful data are, at best, incomplete, examples of promising preventive approaches by nutrient supplementation may potentially be assumed for antioxidants, 17,18 bioactive collagen peptides, 19 and nitrates 20 …”
mentioning
confidence: 99%